PENERAPAN METODE SUGGESTOPEDIA DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 1 BENGKALIS - Putri, Lusi Dwi; Darwis, Muhajir (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
This research is motivated by the fact that the learning methods used are still ineffective, so that students tend to be less motivated in the learning process. This study aims to find out how the suggestopedia method is applied. Then, to find out how much the influence of the suggestopedia method in increasing the learning outcomes of class VIII students in Islamic Religious Education subjects at SMP Negeri 1 Bengkalis. The type of research used in this study was an experiment by taking 2 classes from the population consisting of an experimental class and a control class. Data collection techniques using tests and documentation. This study concluded that after the suggestopedia method was applied, the implications for the implementation of student learning went well. This is because student learning process becomes more optimal. The suggestopedia method can increase the learning outcomes of class VIII students in Islamic Religious Education subjects at SMP Negeri 1 Bengkalis